The Role of Ocular Coherence Tomography in Glaucoma Diagnosis and Management - Anand, Nitin (Pakistan Journal of Ophthalmology, 2014)
New technologies bring with them new hope and often unrealistic expectations. Optical Coherence Tomography (OCT) is no exception. The use of OCT has led to a much better understanding of the structure of the retina. It has, within the space of a few years, become irreplaceable in the management of retinal disorders. Therapy for macular diseases is now guided by OCT findings. Glaucoma is a chronic slowly progressive neuro-pathy of the optic nerve and presents a different challenge. Screening tests generate a large number of false positives and frequently miss early cases. Recent large scale studies have shown that the mean intraocular pressure (IOP) at diagnosis is around 20 mm Hg making it a very poor screening tool1,2. Linking structural changes on the optic nerve head (ONH) to characteristic, functional changes in the field of vision is the cornerstone of glaucoma diagnoses and its management by lowering IOP. In general structural changes appear earlier than changes in visual fields. In the Ocular hypertension study (OHTS), more than half the patients who developed glaucoma from ocular hypertension, did so optic disc changes3. Unfortu-nately our current examination techniques and tests do not allow us to detect the disease early and we often rely on changes of visual field to diagnose glaucoma. It is estimated that at least 35% of the retinal ganglion cells have to be lost before any VF loss appears.